2012
DOI: 10.1371/journal.pone.0037695
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Interacts with Components of the Slit Diaphragm Complex in Podocytes and Is Involved in Podocyte Migration and Permeability In Vitro

Abstract: IQGAP1 is a scaffold protein that interacts with proteins of the cytoskeleton and the intercellular adhesion complex. In podocytes, IQGAP1 is associated with nephrin in the glomerular slit diaphragm (SD) complex, but its role remains ill-defined. In this work, we investigated the interaction of IQGAP1 with the cytoskeleton and SD proteins in podocytes in culture, and its role in podocyte migration and permeability. Expression, localization, and interactions between IQGAP1 and SD or cytoskeletal proteins were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
1
18
0
1
Order By: Relevance
“…Although the question of whether motile podocytes induce proteinuria and renal damage is still controversial, 8,41 it is widely accepted that the reorganization of actin cytoskeleton is necessary for podocyte migration. 40,41,48 Thus, the results of our experiments show that SIRT1 is required for the appropriate reorganization of actin cytoskeleton in podocytes. SIRT1 belongs to the HDAC family, which acts to deacetylate proteins and histones and controls epigenetic changes and protein functions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Although the question of whether motile podocytes induce proteinuria and renal damage is still controversial, 8,41 it is widely accepted that the reorganization of actin cytoskeleton is necessary for podocyte migration. 40,41,48 Thus, the results of our experiments show that SIRT1 is required for the appropriate reorganization of actin cytoskeleton in podocytes. SIRT1 belongs to the HDAC family, which acts to deacetylate proteins and histones and controls epigenetic changes and protein functions.…”
Section: Discussionsupporting
confidence: 51%
“…Because the cellular motility of podocytes is dependent on their dynamic assembly of actin, [38][39][40][41] we hypothesized that podocyte migration ability is attenuated when the regulation of actin cytoskeleton is disorganized by SIRT1 inhibition. To address this, we examined the change in cellular motility by scratch assay.…”
Section: Podocyte Motility Is Reduced By Sirt1 Inhibitionmentioning
confidence: 99%
“…Notably, the closely related protein IQGAP1 was also reported to interact with the podocyte cytoskeleton and components of the SDs, including Nephrin, 31 and to control podocyte motility and permeability in vitro. 32 Together with a recent report on downregulation of IQGAP1 in patients with diabetic nephropathy, 33 both IQGAP isoforms may play a particular role in podocyte biology. Future experiments will have to determine whether IQGAP1 and IQGAP2 possess redundant and/or unique functions and how they are possibly linked to acquired and/or hereditary forms of NS in humans.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, Rigothier et al [32] reported that IQGAP1 regulates podocyte migration and permeability by interacting with components of the slit diaphragm complex. However, its role in podocyte apoptosis is still elusive.…”
Section: Discussionmentioning
confidence: 99%